(untitled) (Al-Academy, 2025)
Since the current research aims to reveal the structural mechanisms of the balance element in industrial product design systems, the researcher adopted the descriptive analytical method to build his research procedures, as it is the most appropriate scientific method to measure the goal of the current research. The research community consists of industrial products that meet the needs and requirements of the consumer, represented by the things he needs to furnish his place, including (seating chairs in different social systems), so the researcher chose (3) industrial models as a sample for the research. The research produced a set of results, the most important of which are: 1-The functional meaning of the shape in the design unit is linked to the user’s memory, mind, and knowledge of it because the shape system and the functional meaning systems depend entirely on the degree of good knowledge of the shapes, their symbols, and the method of use and do not depend on technical characteristics only. 2-The relationship between form and function can be achieved by showing the formal or informal balance between the components of the design unit. The most important conclusions are: 1-Color is an essential factor in the structural system of form within the design unit, as it gives identity to the form, in addition to the semantic meaning that color carries in its various forms that achieve the functional dimension and the aesthetic dimension. 2- They form the luminous values of the light, dark and shaded areas that appear on the structure of the industrial product